Atypical presentation of septic fibroid as uterine perforation - Ajit Nagarsenkar,; Guruprasad Pednecar,; Roy Menezes,; Ankush Dessai,; Viraj Khandeparker, (Indian Journal of Case Reports, 2021)
Pyomyoma, also known as suppurative leiomyoma, is a rare complication of uterine leiomyoma which arises due to infarction, degeneration, and subsequent infection of a pre-existing leiomyoma. This report highlights the case of a 52-year-old patient who presented to the emergency department with complaints of fever, abdominal pain, and breathlessness. She was a known case of fibroid uterus. She also had uncontrolled diabetes mellitus and bilateral renal calculi. The patient was diagnosed to have diabetic ketoacidosis with shock and was admitted to the intensive care unit. Computed tomography scan showed incidental findings of rent in the fundus of the uterus suggestive of uterine perforation. After stabilization of the patient, laparotomy was done which revealed the uterus to be enlarged to 14 weeks size. There was a 3 cm × 3 cm perforation on the fundoposterior surface of the uterus with purulent discharge. A decision was taken for total abdominal hysterectomy. The patient had a remarkable improvement postoperatively.